Contest as the form to acquire most excellent design solution in spatial planning, urban planning and architecture - Jarosław Oglęcki (Economic and Environmental Studies (E&ES), 2016)
In this article, basing on available studies of public procurement forms of design services in spatial planning, urban planning and architecture, was attested that, with fulfilling high organizational standards, most excellent form is contest. It ensures the choice of studies which in the best way take into the consideration criteria of city development balance and offer the highest quality of design solutions. In the later stadium of realization the design solutions have crucial influence on urban space.
Keywords: R51; R58; 330; balanced city development; architecture; contest